Analysis of the Mechanism for the Development of Allergic Skin Inflammation and the Application for Its Treatment: Establishment of a Modified Allergic Dermatitis Model in Mouse Ear Lobes by Application of 12-O-Tetradecanoyl Phorbol 13-Acetate: Putative Involvement of Thymic Stromal Lymphopoietin and Roles of Histamine - Noriyasu Hirasawa; Yuhsuke Ohsawa; Kenji Ishihara; Toshio Seyama; JangJa Hong; Kazuo Ohuchi (Elsevier, 2009)
Abstract.: We established a novel allergic dermatitis model in mouse ear lobes in which antigen-nonspecific inflammation was induced by painting 12-O-tetradecanoylphorbol 13-acetate (TPA) between sensitization and challenge with picryl chloride (PiCl). This model has an advantage for analyzing atopic dermatitis-like inflammation within a short period. Analysis of the time course changes in the PiCl-induced swelling showed that the allergic inflammation was shifted from a delayed-type response to a biphasic response consisting of a weak immediate-phase response and a late-phase response by painting with TPA. The application of TPA increased the PiCl-induced infiltration of eosinophils and mast cells at the inflammatory site and shifted the cytokine milieu from Th1 to Th2. The expression of the Th2-inducing cytokine thymic stromal lymphopoietin (TSLP) mRNA was also increased by TPA. These findings suggested that the induction of antigen-nonspecific inflammation by TPA before the antigen challenge enhanced the Th2 response and modified the PiCl-induced delayed type-hypersensitivity. Using this model, we clarified that histamine plays significant roles in the early-phase swelling via H1 receptors and the late-phase swelling via H3/H4 receptors. Thus, we suggested the usefulness of the combined treatment with an H1 antagonist and an H4 antagonist for the suppression of atopic dermatitis. Keywords:: allergic dermatitis, histamine, picryl chloride, 12-O-tetradecanoylphorbol 13-acetate, thymic stromal lymphopoietin, allergic inflammation